MANAGEMENT MODEL FOR EXCELLENT SERVICE OF SANPATONG DISTRICT SERVICE UNIT OF SPECIAL EDUCATION CENTER EDUCATIONAL SERVICE AREA 8, CHIANG MAI PROVINCE, UNDER THE OFFICE OF SPECIAL EDUCATION ADMINISTRATION - Tano, Prapai; Boonsong, Kanchana; Srirangsan, Chulaporn (Journal of MCU Phetchaburi Review, 2025)
This research aimed to 1) develop a management model for excellent service in Sanpatong District Service Unit and 2) study the results of using the management model for excellent service in Sanpatong District Service Unit. The target group used in the research was 33 people. The research instruments consisted of 1) a manual for using the model, 2) a model evaluation form, 3) a basic development assessment form for disabled students, and 4) a satisfaction evaluation form. The statistics used in data analysis were frequency, percentage, mean, and standard deviation. The research results found that; The management model for excellent service of Sanpatong District Service Unit is the 3S4Smart Model, consisting of the following 7 components: Strategic Planning, Structure organizational, Style of Management, Smart Director, Smart teacher, Smart Student, and Smart Team. 2. The results of using the management model for excellent service in Sanpatong District Service Unit found that the target population is most satisfied with the use of the management model for excellent service at the Sanpatong District Service Unit. When considering the average values ​​from most to least for each component, it was found to be at the highest level in all aspects. And the disabled children who received services from the Sanpatong District Service Unit had an average percentage of scores after using the management model that increased from before use, which was 73.49 percent, which is at an excellent level.